Genome-Wide Association Study of MKI67 Expression and its Clinical Implications in HBV-Related Hepatocellular Carcinoma in Southern China - Cheng-kun Yang; Ting-dong Yu; Chuang-ye Han; Wei Qin; Xi-wen Liao; Long Yu; Xiao-guang Liu; Guang-zhi Zhu; Hao Su; Si-cong Lu; Zhi-wei Chen; Zhen Liu; et al. (Cellular Physiology and Biochemistry, 2017)
Background/Aims: Hepatocellular carcinoma (HCC) is a common malignant tumor with a high rate of recurrence. Immunohistochemical analysis of the marker of proliferation Ki-67 (MKI67) is used to assess proliferation activity of HCC The regulation of MKI67 expression remains unclear in HCC This study aims to explore the association between MKI67 expression and gene variants. Methods: A total of 195 hepatitis B virus (HBV)-related HCC patients were genotyped using Illumina HumanExome BeadChip-12-1_A (242,901 markers). An independent cohort (97 subjects) validated the association of polymorphism determinants and candidate genes with MKI67 expression. The relationships between MKI67 with p53 and variants of candidate genes in the clinical outcomes of HCC patients were analyzed. Results: We found that MKI67 combined with p53 was associated with a 3-year recurrence-free survival and five variants near TTN and CCDC8 were associated with MKI67 expression. TTN harboring rs2288563-TT and rs2562832-AA+CA indicated a favorable outcome for HCC patients. Conclusion: Variants near TTN and CCDC8 were associated with MKI67 expression, and rs2288563 and rs2562832 in TTN are potential biomarkers for the prediction of clinical outcomes in HBV-related HCC patients.